2015
DOI: 10.1111/spol.12144
|View full text |Cite
|
Sign up to set email alerts
|

Europe 2020 and the Fight against Poverty – Beyond Competence Clash, Towards ‘Hybrid’ Governance Solutions?

Abstract: The supranational strategy ‘Europe 2020’ came along with two main innovations for social policy coordination in the EU: a quantified poverty reduction target and a new governance framework – the ‘European Semester’. Aiming to assess the effectiveness of the novel strategy in prompting the emergence of a European(‐ized) anti‐poverty arena – thus inherently multilevel and multi‐stakeholder, as well as integrated (across policy sectors) – the article first presents the strategy evolution at the supranational leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Linkov's work further unpacks the various notations of collaborative and multistakeholder governance for extreme system complexity and uncertainty (Linkov et al) [6]. Jessoula studied the effectiveness of multiagent collaborative poverty alleviation from the perspective of multilevel social structure in Europe [7]. Khumalo advocated a multistakeholder approach to the challenge of poverty and reconsidered the structural issue of perpetuating poverty [8].…”
Section: Literaturementioning
confidence: 99%
“…Linkov's work further unpacks the various notations of collaborative and multistakeholder governance for extreme system complexity and uncertainty (Linkov et al) [6]. Jessoula studied the effectiveness of multiagent collaborative poverty alleviation from the perspective of multilevel social structure in Europe [7]. Khumalo advocated a multistakeholder approach to the challenge of poverty and reconsidered the structural issue of perpetuating poverty [8].…”
Section: Literaturementioning
confidence: 99%
“…For Crespy and Menz () social policy concerns have been further marginalized in the new governance arrangements. Zeitlin and Vanhercke (), Bekker () and Jessoula () have been considerably more positive, arguing that from 2012 onwards social actors were able to navigate the European Semester and advance social issues, as evidenced by increased visibility and activity in the social policy sphere, including a greater social focus in the CSRs. We seek to deepen knowledge, by bringing new evidence and more penetrating analyses to bear on the EU approach.…”
Section: Introductionmentioning
confidence: 99%
“…to reposition their problem perceptions and interpretations, interests and strategies of action within a European framework (Eder 2004;Trenz and Eder 2004), thus generating new conflict lines (Fligstein 2008;Vobruba 2014). Even in areas where the EU does not have its own legislative powers with "hard" rights of intervention, the expansion logic is not invalidated, as research on Europe has indicated that the EU has developed "soft" management and coordination instruments to achieve unification and harmonisation goals also in these fields (Hodson and Maher 2001;Mosher and Trubek 2003;Jessoula 2015). In this context, it was noted that the EU is very successful in the diffusion and creeping convergence of political problem diagnoses, proposed solutions and regulatory ideas (Featherstone and Radaelli 2003).…”
Section: Antipodes and Correlates: The European And The National Spherementioning
confidence: 99%